Analyzing two different data processing strategies for monitoring concrete structures using ultrasonic pulse velocity - Lorenzi, A.; Fonseca Caetano, L.; Campagnolo, J. L.; Pinto da Silva Filho, L. C. (Revista ALCONPAT, 2012)
The increasing number of early deterioration symptoms found in relatively new concrete structures provides a strong argument for the development and validation of techniques to monitor the condition state of concrete elements and provide data to estimate the potential service life. The use of NDT monitoring techniques is an important way to prevent and control the deterioration of concrete structures without damaging the material. Ultrasonic Pulse Velocity (UPV) measurements seem to be a quite effective way to perform quality control, since this reliable and flexible test method allows an in-depth analysis of the material’s condition. Using UPV data it is possible to check the concrete uniformity, accompany the deterioration, detect internal flaws and voids and, by means of a comparison with reference specimens, even estimate the compressive strength. The results indicate that surface mapping seems to be a better way toanalyze and visualize UPV results.